Primary lateral sclerosis (PLS) functional rating scale: PLS‐specific clinimetric scale. Issue 2 (13th December 2019) - Mitsumoto, Hiroshi; Chiuzan, Codruta; Gilmore, Madison; Zhang, Yuan; Simmons, Zachary; Paganoni, Sabrina; Kisanuki, Yasushi Y.; Zinman, Lorne; Jawdat, Omar; Sorenson, Eric; Floeter, Mary Kay; Pioro, Erik P.; et al.
Abstract: Introduction: Our research aim was to develop a novel clinimetric scale sensitive enough to detect disease progression in primary lateral sclerosis (PLS). Methods: A prototype of the PLS Functional Rating Scale (PLSFRS) was generated. Seventy‐seven participants with PLS were enrolled and evaluated at 21 sites that comprised the PLSFRS study group. Participants were assessed using the PLSFRS, Neuro‐Quality of Life (QoL), Schwab‐England Activities of Daily Living (ADL), and the Clinical Global Impression of Change scales. Participants completed telephone assessments at 12, 24, and 48 weeks after enrollment. Results: The PLSFRS demonstrated internal consistency as well as intrarater, interrater, telephone test‐retest reliability, and construct validity. Significant changes in disease progression were detected at 6 and 12 months; changes measured by the PLSFRS vs the ALSFRS‐R were significantly higher. Discussion: The PLSFRS is a valid tool to assess the natural history of PLS in a shorter study period.